Свое - чужое в языке и речи - Külmoja, Irina (Acta Slavica Estonica, 2016)
Acta Slavica Estonica is an international series of publications on current issues of Russian and other Slavic languages, literatures and cultures. One of the fundamental oppositions of the semiotics of culture - between "own" (native) and "alien" (foreign) - is also important for the language, which is the foundation of any ethnic culture and in which "our own", originally inherent in a given language, constituting its basis, and elements of the "alien" at different levels of the language always coexist. The articles in this collection make their contribution to the study of the cultural and social characteristics of the language by studying the complex interaction of "own" and "alien" in language and speech.